2022
DOI: 10.3390/v14050985
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and Arthropods: A Review

Abstract: The emergence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) that led to the unprecedented COVID-19 pandemic exemplifies how a lack of understanding and preparedness for emerging viruses can result in consequences on a global scale. Statements that SARS-CoV-2 could not be transmitted by arthropod vectors were made without experimental support. Here we review laboratory-based research, field studies, and environmental studies to evaluate the potential for the virus to be transmitted either biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Although the ACE2 receptor in insects differs significantly from that of mammals, making efficient binding with SARS-CoV-2 unlikely, it has been reported that arthropods were involved in the mechanical transmission of the turkey coronavirus, parapoxvirus, and SARS-CoV-2 [58,59]. Experimental studies have demonstrated that houseflies may be a vector for SARS-CoV-2 genomic RNA transmission to the surrounding environment up to 24 h post-exposure [60]. Finally, it is advisable to implement a monitoring program to assess the potential presence of SARS-CoV-2 in WWTP using PCR techniques or biosensor-based technologies, which have been extensively employed for virus detection.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ACE2 receptor in insects differs significantly from that of mammals, making efficient binding with SARS-CoV-2 unlikely, it has been reported that arthropods were involved in the mechanical transmission of the turkey coronavirus, parapoxvirus, and SARS-CoV-2 [58,59]. Experimental studies have demonstrated that houseflies may be a vector for SARS-CoV-2 genomic RNA transmission to the surrounding environment up to 24 h post-exposure [60]. Finally, it is advisable to implement a monitoring program to assess the potential presence of SARS-CoV-2 in WWTP using PCR techniques or biosensor-based technologies, which have been extensively employed for virus detection.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ACE2 receptor in insects differs significantly from that of mammals, making efficient binding with SARS-CoV-2 unlikely it has been reported that arthropods were involved in the mechanical transmission of the turkey coronavirus, parapoxvirus, and SARS-CoV-2 [52,53]. Experimental studies have demonstrated that houseflies may be a vector for SARS-CoV-2 genomic RNA transmission to the surrounding environment up to 24 h post-exposure [54]. Finally, it is advisable to implement a monitoring program to assess the potential presence of SARS-CoV-2 in WWTP using PCR techniques or biosensor-based technologies, which have been extensively employed for virus detection.…”
Section: Discussionmentioning
confidence: 99%